(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Rivers have essential role in human cultures. They are sanctuary for amount of biodiversity, but threatened seriously now. The objective of this research is to know Surakarta (Solo) rivers quality based on plankton diversity. This town has amount of kampongs and industrial estates that discard wastes to rivers directly. Plankton community is one of the river qualities indicators, because pollutant and other organisms can influence their population. The research was conducted at four rivers in Surakarta, namely Pepe River, Premulung River, Anyar River and Jenes River. Data was collected in triple before and after rivers through the town. Data was analyzed by diversity index of Shannon Wienner. The result indicated that Surakarta rivers had been polluted in degree of lightly to seriously. Â© 2002 Jurusan Biologi FMIPA UNS Surakarta Key words: bioindicator, plankton, pollutant, river, Surakarta (Solo) town.